Stanislavski's best student directs: Maria Lilina's first and last production. Issue 1 (2nd January 2016) - Ignatieva, Maria
Abstract: Stanislavski's wife Maria Lilina (1866-1943) was his ideal student (by his own admittance) and his faithful artistic follower. Lilina was the only actor who worked with the master throughout all the stages of the System in its 30-year formation, hence Stanislavski charged her with a special project at the Opera-Dramatic Studio. As a director, Lilina was to base the rehearsals of The Cherry Orchard on his most recent ideas, and to seek the artistic proof of his theory. Stanislavski asked Lilina to work on the play, having categorically forbidden the students to use the text or even to read the play. Lilina would give the detailed descriptions of the act or the scene in the beginning of the rehearsal, after which students would improvise. Every time Lilina carefully guided them toward the true meaning of the scene, as she and Stanislavski had discussed it prior to every rehearsal. After months of successful rehearsals, one of the other pedagogues of the Opera-Dramatic Studio was permitted to read the act to the students out loud. Stanislavski's death in 1938 and Hitler's invasion of the USSR in 1941, then Lilina's death in 1943 did not allow these rehearsals to reach fruition in a theatre production; however, the rehearsal diaries and the memoirs of the participants shed light upon the unique rehearsal process and Lilina's use of the method of active analysis. The study also allows us to see the further alienation of Stanislavski's acting theories from the work on the text of the play, and the play itself as the foundation of a theatre production.